Functional profile of antigen specific CD4+ T Cells in the Immune response to phospholipase a1 allergen from polybia paulista Venom - Fernandes, Lu s Gustavo Romani (2020)
Insect venom can cause systemic allergic reactions, including anaphylaxis. Improvements in diagnosis and venom immunotherapy (VIT) are based on a better understanding of an immunological response triggered by venom allergens. Previously, we demonstrated that the recombinant phospholipase A1 (rPoly p 1) from Polybia paulista wasp venom induces specific IgE and IgG antibodies in sensitized mice, which recognized the native allergen. Here, we addressed the T cell immune response of rPoly p 1-sensitized BALB/c mice. Cultures of splenocytes were stimulated with Polybia paulista venom extract and the proliferation of CD8+ and CD4+ T cells and the frequency of T regulatory cells (Tregs) populations were assessed by flow cytometry. Cytokines were quantified in cell culture supernatants in ELISA assays. The in vitro stimulation of T cells from sensitized mice induces a significant proliferation of CD4+ T cells, but not of CD8+ T cells. The cytokine pattern showed a high concentration of IFN- and IL-6, and no significant differences to IL-4, IL-1 and TGF- 1 production. In addition, the rPoly p 1 group showed a pronounced expansion of CD4+CD25+FoxP3+ and CD4+CD25-FoxP3+ Tregs. rPoly p 1 sensitization induces a Th1/Treg profile in CD4+ T cell subset, suggesting its potential use in wasp venom immunotherapy.